MATHEMATICAL MODELLING OF CONSUMER CHOICE IN FASHION: POTENTIAL STUDENT PROJECTS (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2015)
This paper suggests an unusual theme for undergraduate student projects. The future is now.  Repackaging the past has historical value but it is not a preparation for the range and scope of the internet as a vast copying machine which can not only detect purchasing patterns but can adjust bargain prices to fit the buyers calculated financial power and target them through intermediary subsidiaries in a universal online market. Quantitative techniques can now penetrate disciplines which once eschewed them. This paper looks at three such approaches in the context of consumer choice in fashion.